1995
DOI: 10.1136/jmg.32.3.234
|View full text |Cite
|
Sign up to set email alerts
|

Renal tubular leakage complicating microcephalic osteodysplastic primordial dwarfism.

Abstract: We describe a male infant with phenotypic and radiological features

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Three cases reported as MOPD I share some of the facial and musculoskeletal features but differ in significant ways such as arachnodactyly, large ears, corneal clouding and hirsutism (9); generalized renal tubular leakage with persistent hyponatremia, hypokalemia, hypocalcemia, and hypophosphatemia, and normal scalp hair (13); and osteoporosis, multiple fractures, hepatosplenomegaly, cholestasis without evidence of storage disease, focal renal medullary dysplasia, and normal scalp hair (14). The probable presence of varied metabolic abnormalities in these three reports does not appear to be consistent with the previously observed phenotypes of MOPD I. Genotyping of these cases for mutations in RNU4ATAC and other microcephalic primordial dwarfism (MPD) genes will be helpful in clarifying the true extent of the MOPD I phenotype.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three cases reported as MOPD I share some of the facial and musculoskeletal features but differ in significant ways such as arachnodactyly, large ears, corneal clouding and hirsutism (9); generalized renal tubular leakage with persistent hyponatremia, hypokalemia, hypocalcemia, and hypophosphatemia, and normal scalp hair (13); and osteoporosis, multiple fractures, hepatosplenomegaly, cholestasis without evidence of storage disease, focal renal medullary dysplasia, and normal scalp hair (14). The probable presence of varied metabolic abnormalities in these three reports does not appear to be consistent with the previously observed phenotypes of MOPD I. Genotyping of these cases for mutations in RNU4ATAC and other microcephalic primordial dwarfism (MPD) genes will be helpful in clarifying the true extent of the MOPD I phenotype.…”
Section: Resultsmentioning
confidence: 99%
“…It was subsequently suggested that types I and III were part of the same clinical spectrum with subtle variations among brain anomalies and radiographic changes (4); the two types have generally been combined since that time. Only 31 individuals with MOPD I/III from 25 families worldwide were reported in the literature through to 2010 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
mentioning
confidence: 99%
“…Malformations of the central nervous system have been reported [Winter et al, 1985;Haan et al, 1989;Meinecke and Passarge, 1991; Table III], such as abnormalities of migration, neuronal heterotopias, partial or complete agenesis of the corpus callosum, hypoplastic frontal lobes, and vermis agenesis. Tetralogy of Fallot and renal tubular leakage were described in single cases [Majewski and Spranger, 1976;Eason et al, 1995]. The patient reported by Van Maldergem et al [1990] exhibited unusual manifestations such as corneal clouding, arachnodactyly, and general hirsutism.…”
Section: Discussionmentioning
confidence: 99%
“…MOPD I was first described by Taybi and Linder [1967] as cephaloskeletal dysplasia and fewer than 30 cases have been reported [Thomas and Nevin, 1976; Winter et al, 1985; Haan et al, 1989; Meinecke and Passarge, 1991; Meinecke et al, 1991; Eason et al, 1995; Berger et al, 1998; Sigaudy et al, 1998; Vichi et al, 2000; Klinge et al, 2002; Juric‐Sekhar et al, 2011]. Skeletal findings in MOPD I include platyspondyly and vertebral clefting, horizontal acetabular roofs, elongated and curved clavicles, and short long bones with enlarged metaphyses including age‐dependent bowing and undermodeled long bones.…”
Section: Introductionmentioning
confidence: 99%